EFEKTIFITAS EDUKASI KESEHATAN DENGAN METODE TELENURSING DALAM MENANGGULANGI KECENDERUNGAN SIKAP SEKS BEBAS PADA REMAJA - Tiwow, Irene; Rakinaung, Natalia; Geneo, Martinus; Budiawan, Helly (Lasalle Health Journal, 2022)
Introduction: Free sex is a sexual behavior that is driven by a desire carried out by both the same sex and the opposite sex without any marriage ties. However, there are still many adolescent who fall into free sex. This can make many generations of young people drop out of school due to free sex and sexually transmitted diseases can occur. Objective: The purpose of this study is to provide health education about the impact of free sex on adolescents by using telenursing method which is expected to increase adolescents' good attitudes towards free sex. Method: This research is a quantitative research with a quasi-experimental research design with one group pre and post-test. Respondents from this study were adolescent who lived in Sarongsong 1 Village, North Minahasa Regency, North Sulawesi Province. Indonesia. Respondent in this research are 23 adolescent by using a total sampling technique. The statistical test used in this study was paired t-test with a significant value p-value<0.05. Results: The results showed the attitude of the respondents during the pretest; the mean is 65.70 and the post-test is 73.70 with P-value = 0.000. Conclusions: so, it can be concluded that health education about the impact of free sex on adolescents using the telenursing method is significantly effective in increasing adolescents' good attitudes towards free sex. It is hoped that the results of this study can add insight to nurses about health education methods for adolescents, especially related to free sex and hopefully health education about the impact of free sex on adolescents by using telenursing method can be used in health services for adolescents.